1996
DOI: 10.1016/0921-4534(96)00266-3
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible magnetization in thin YBCO films rotated in external magnetic field

Abstract: The magnetization M of a thin Y Ba 2 Cu 3 O 7−δ film is measured as a function of the angle θ between the applied field H and the c− axis. For fields above the first critical field, but below the Bean's field for first penetration H * , M (θ)is symmetric with respect to θ = π and the magnetization curves for forward and backward rotation coincide. For H > H * the curves are asymmetric and they do not coincide. These phenomena have a simple explanation in the framework of the Bean critical state model.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 23 publications
3
7
1
Order By: Relevance
“…It has been shown [9][10][11] that, in this fully penetrated critical state and as long as ν tan Θ ≪ 1, the angle between M i and the sample normal n is α ∼ arctan 2 3 ν 2 tan Θ ≪ Θ. That is, M i remains almost locked to n due to a purely geometrical effect.…”
Section: B Critical Statementioning
confidence: 98%
See 3 more Smart Citations
“…It has been shown [9][10][11] that, in this fully penetrated critical state and as long as ν tan Θ ≪ 1, the angle between M i and the sample normal n is α ∼ arctan 2 3 ν 2 tan Θ ≪ Θ. That is, M i remains almost locked to n due to a purely geometrical effect.…”
Section: B Critical Statementioning
confidence: 98%
“…A rotation at fixed H is to some extent analogous to a hysteresis loop 9 . Rotating n towards H increases H ⊥ , which is roughly equivalent to increasing H at Θ = 0 • , moving along the lower (diamagnetic) branch of the loop.…”
Section: B Critical Statementioning
confidence: 99%
See 2 more Smart Citations
“…Experiments have generally shown good agreement [12,13] with the critical state model despite the effects of vortex curving. In particular it has been shown by Prozorov et al [14] that the critical state magnetization of thin films is contributed overwhelmingly by the component parallel to the c-axis and that the a-b-plane moment is negligible. This has been further elaborated by Zhukov et al [15] who showed that this effect originates in the extremely large aspect ratio of the thin films.…”
Section: Introductionmentioning
confidence: 99%